The Effect of Protein Feed Supplementation to Various Roughage Basal Feed on The Performance of Bligon Goats - Kustantinah (Kustantinah); H. Hartadi; L. M. Yusiati; R. Utomo; A. Agus; B. Suhartanto; F. Holil; E. Dahono (Faculty of Animal Science, Universitas Gadjah Mada, 2005)
File lengkap ada dalam bentuk PDF dibawah ini